Media kincir angka: Inovasi pembelajaran non-digital untuk menguatkan nilai akhlak dan keimanan pada siswa madrasah aliyah - Abdallillah, Najwa Aisyah; Aliyah, Avina Faizatul; Maulidia, Arin Nafisa (Maliki Interdisciplinary Journal, 2025)
This research aims to examine the use of the Kincir Angka media as a means of character building for students through the material of praiseworthy morals, reprehensible morals, and faith in Qadha' and Qadar. The Kincir Angka media, which has been known to be effective in improving children's cognitive abilities in recognizing numbers, was developed as an interactive and interesting learning tool to instill positive character values in students. The research method uses a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Furthermore, in the design and development stage, the Kincir Angka media was modified in such a way as to suit the content of the morals and faith material taught in the curriculum. The implementation stage was carried out through integrated thematic learning, where students were actively involved in the process of playing while learning. The evaluation results showed that the use of this media was able to improve students' understanding of the material and shape attitudes and behaviors that reflect the expected character values.